The Potential of Eukaryotic Cell-Free Systems as a Rapid Response to Novel Zoonotic Pathogens: Analysis of SARS-CoV-2 Viral Proteins - Ramm, Franziska; Dondapati, Srujan K.; Trinh, Hoai Anh; Wenzel, Dana; Walter, Ruben M.; Zemella, Anne; Kubick, Stefan (Frontiers in Bioengineering and Biotechnology, 2022)
The ongoing pandemic caused by the novel coronavirus (SARS-CoV-2) has led to more than 445 million infections and the underlying disease, COVID-19, resulted in more than 6 million deaths worldwide. The scientific world is already predicting future zoonotic diseases. Hence, rapid response systems are needed to tackle future epidemics and pandemics. Here, we present the use of eukaryotic cell-free systems for the rapid response to novel zoonotic diseases represented by SARS-CoV-2. Non-structural, structural and accessory proteins encoded by SARS-CoV-2 were synthesized by cell-free protein synthesis in a fast and efficient manner. The inhibitory effect of the non-structural protein 1 on protein synthesis could be shown in vitro. Structural proteins were quantitatively detected by commercial antibodies, therefore facilitating cell-free systems for the validation of available antibodies. The cytotoxic envelope protein was characterized in electrophysiological planar lipid bilayer measurements. Hence, our study demonstrates the potential of eukaryotic cell-free systems as a rapid response mechanism for the synthesis, functional characterization and antibody validation against a viral pathogen.